Intraclonal genome diversity of the major Pseudomonas aeruginosa clones C and PA14. Issue 2 (28th January 2016) - Fischer, Sebastian; Klockgether, Jens; Morán Losada, Patricia; Chouvarine, Philippe; Cramer, Nina; Davenport, Colin F.; Dethlefsen, Sarah; Dorda, Marie; Goesmann, Alexander; Hilker, Rolf; Mielke, Samira; Schönfelder, Torben; et al.
Summary: Bacterial populations differentiate at the subspecies level into clonal complexes. Intraclonal genome diversity was studied in 100 isolates of the two dominant P seudomonas aeruginosa clones C and PA14 collected from the inanimate environment, acute and chronic infections. The core genome was highly conserved among clone members with a median pairwise within‐clone single nucleotide sequence diversity of 8 × 10 −6 for clone C and 2 × 10 −5 for clone PA14. The composition of the accessory genome was, on the other hand, as variable within the clone as between unrelated clones. Each strain carried a large cargo of unique genes. The two dominant worldwide distributed P . aeruginosa clones combine an almost invariant core with the flexible gain and loss of genetic elements that spread by horizontal transfer.